Direct Molecular Detection and Phylogenetic Relationship of Staphylococcus aurous from Mastitis Milk in Sheep and Cows - Esraa T.M. (Journal of Global Pharma Technology, 2016)
The present study included the direct detection of Staphylococcus aurous isolated from milk of sheep and cows  infected by mastitis based 16SrRNA gene by PCR technique and study the phylogenetic relationship analysis based on spa gene of using DNA sequence method.  The study includes collected 32 sheep and 45 cow’s mastitis milk samples. These samples were submitted to milk DNA extraction, and then performed PCR technique. The PCR results were showed significant at P value: (< 0.05) in prevalence between sheep and cow Staphylococcus aurous positive isolates at (5/15.5%) and (14/31.1%) respectively.  DNA sequencing of partial sequence of spa gene was showed Staphylococcus aureus sheep isolate was genetic relationship analysis different than cow isolate and related to NCBI-Blast Staphylococcus aureus isolate H13939 (AM407304.1) at  (99%) homology sequence identity and NCBI-Blast Staphylococcus aureus strain AO124 (JX912490.1) at  (94%) homology sequence identity total genetic change (0.005). In conclusion, Staphylococcus aurous isolated from mastitis milk in sheep and cows were not related genetically. Therefore, Spa gene analysis was provides an efficient method for investigating phylogenetic relationships among different clinical isolates and can be useful for monitoring distribution of pathogen related to public health.Keywords: Staphylococcus aureus, Milk, Sheep, Cow, PCR, 16SrRNA, spa gene.